Performance of Power Systems Under Sustained Random Perturbations - Verdejo-Fredes, H (Hindawi Limited, 2014)
This paper studies linear systems under sustained additive random perturbations. The stable operating point of an electric power system is replaced by an attracting stationary solution if the system is subjected to (small) random additive perturbations. The invariant distribution of this stationary solution gives rise to several performance indices that measure how well the system copes with the randomness. These indices are introduced, showing how they can be used for the optimal tuning of system parameters in the presence of noise. Results on a four-generator two-area system are presented and discussed. © 2014 Humberto Verdejo et al.